A study of the accounting system of a Haulier Company (Shapadu Kontena Sdn. Bhd.) in particular its internal control / Md Nor Azam Ariffin - Ariffin, Md Nor Azam (1987)
Containerisation is said to have started in 1963 when the first 'Sea land' service commenced from Puerto Rico to Baltimore in the United States. The concept of containerisation is essentially the provision of door-to-door service from the point of in-land distribution to a destination.